Tuberculosis manual for obstetricians and gynecologists - Tripathy, S. N.; Tripathy, Sindhu Nandini (Jaypee Brothers Medical Publishers (P) Ltd., 2015)
This book is a comprehensive guide to the diagnosis and management of tuberculosis in obstetric and gynaecological patients. The book focuses on the endometrium (the inner membrane of the uterus) in cases of pulmonary tuberculosis. Divided into five sections, the book begins with the history of tuberculosis, including an overview of tuberculosis in the 21st century, and features discussion on the relationship between nutrition in pregnancy and tuberculosis